Tender boost - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Papaya production on the Fiji Islands has steadily increased from 400 t in 1992 to more than 2,600 t in 2000. The pink fleshed Sunrise Solo is an especially popular exportable variety. The construction of a heat treatment facility for meeting pest...